Maintenance of the buccal fat pad (Bichat) as a resource for regional grafting: A case report and literature review - Rodrigues, Luana Queila; Santos Netto, Alfredo; Silva, Vinícius Teixeira; Leone, Caroline; de-Campos, Wladimir Gushiken; Lemos, Celso Augusto (Journal of Oral Diagnosis, 2022)
Objective: Report a case of pyogenic granuloma with two years of evolution, three previous removals with external oral and maxillofacial surgeons, and new recurrences. Case Report: A 25-year-old male patient with a history of a pyogenic granuloma with two years of evolution had three previous removals with external maxillofacial and had relapses. The treatment indicated after these relapses were the extraction of the involved teeth and the lesion, performing the closure with a buccal fat pad flap. The lesion underwent metaplasia, transforming into mucosa. Conclusion: This case emphasizes keeping the buccal fat pad as a possible future resource for regional grafting.